Ghrelin’s potential as a therapeutic target for chronic inflammatory diseases: evidence from human endometrial stromal cells - Dong, Wenhui; Mu, Hongkai; Jia, Fan; Wei, Yingying; Lv, JingJing; Zhou, Shizhao; Yu, Shiping; Liang, Tingting (Frontiers in Endocrinology, 2025)
BackgroundGhrelin, a peptide composed of 28 amino acids, is recognized for its role in regulating appetite and energy balance. Recently, it has also been identified as an immunomodulator that could significantly influence immune responses in chronic inflammatory conditions. The role of ghrelin on cell viability and cytokine expression is presented here for human endometrial stromal (hEM15A) cells, with attention to the way this peptide could modulate inflammation.MethodsIn this study, the hEM15A cells were cultured and treated with Ghrelin at concentrations ranging from 1 μM to 1000 μM. Cell viability was assessed using the Cell Counting Kit-8 (CCK-8) assay. Levels of the cytokines TNF-α, IL-6, and IL-10 were measured by ELISA, and the expression of the Ghrelin receptor was confirmed through Western blot (WB) analysis.ResultsThe results demonstrated successful expression of the Ghrelin receptor (GHSR) in hEM15A cells. Analysis of cell viability indicated that Ghrelin positively affected cell proliferation, particularly at higher concentrations. ELISA results showed a significant decrease in pro-inflammatory cytokines TNF-α and IL-6, coupled with a notable increase in the anti-inflammatory cytokine IL-10, in a dose-dependent manner.ConclusionGhrelin can exert its effects through its receptor GHSR. Meanwhile, Ghrelin stimulates cell growth without causing decrease in viability; it has cell protective effect by regulating inflammation at the molecular level by balancing the release of some key pro-inflammatory cytokines. This study discovered and validated the anti-inflammatory effect of Ghrelin in patients with endometriosis. Thus, the data presented open a potential use of Ghrelin as therapy for chronic inflammation-related disorders as endometriosis.